2014
DOI: 10.2134/jeq2013.09.0367
|View full text |Cite
|
Sign up to set email alerts
|

Cadmium Concentrations in New Zealand Pastures: Relationships to Soil and Climate Variables

Abstract: Cadmium (Cd) is a nonessential element that occurs at above-background concentrations in many New Zealand (NZ) soils. Most of this Cd is due to the historical application of single superphosphate that was made from Nauru phosphate rock containing between 400 and 600 mg Cd kg P. Pasture Cd uptake exacerbates the entry of Cd into animal products. We sought to determine the critical environmental factors affecting Cd uptake in NZ pastures and to calculate the likely Cd intake of sheep and cattle. We tested 69 pas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
31
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(38 citation statements)
references
References 36 publications
7
31
0
Order By: Relevance
“…The results display a mean rootsquare error value of 0.17 and a variance (R 2 ) of 0.63, thus defining a good fit. Table 3 summarizes the PA analysis results of The moist environment increases the biological activity, producing soil acidity (Reiser et al, 2014). The study area is characterized by a dense network of rivers (Fig.…”
Section: Correlation With Environmental Factorsmentioning
confidence: 99%
“…The results display a mean rootsquare error value of 0.17 and a variance (R 2 ) of 0.63, thus defining a good fit. Table 3 summarizes the PA analysis results of The moist environment increases the biological activity, producing soil acidity (Reiser et al, 2014). The study area is characterized by a dense network of rivers (Fig.…”
Section: Correlation With Environmental Factorsmentioning
confidence: 99%
“…In the US, 600 000 hm 2 of fields are suffering heavy metal pollution that need to be restored [19] . In New Zealand, it was found out that in some pastures there Cd content in soil was beyond the background value [6] . In the communiques issued by China's Ministry of Environment Protection and Ministry of State Land and Resource, it shows that Cd point beyond standard by 7% ranking the first among various heavy metal contamination, of which those of minus, slight, medium and heavy levels take 5.2%, 0.8%, 0.5% and 0.5% respectively [20] .…”
Section: The Present Global Situation Of Cd-contaminationmentioning
confidence: 99%
“…Nowadays Cd is widely used for electroplating, chemical industry, electronic industry and nuclear industry. Due to discharge of industrial waste water, waste gas, solids as well as irrigation with polluted water, and application of Cd containing pesticides and fertilizer (especially phosphorus contained fertilizer) and organic fertilizer, huge areas of land are polluted by Cd [3][4][5][6][7] . It is easily absorbed by plants that in soil of fields contaminated by cadmium which is then accumulated in human bodies as foods through the food chain [8] .…”
Section: Introductionmentioning
confidence: 99%
“…Such relationship between soil pH and plant Cd has been widely reported in the literature [19,[31][32][33]56]. Wang et al [31] reported that the extractable Cd increased with lowering of soil pH and resulted in enhancing phytoextraction.…”
Section: Change In Plant CD Concentration and Uptakementioning
confidence: 78%
“…Wang et al [31] reported that the extractable Cd increased with lowering of soil pH and resulted in enhancing phytoextraction. Reiser et al [56] also showed that soil pH , soil Fe and soil Cd provided an excellent predictor of the Ca (NO 3 ) 2 -extractable soil Cd fraction, but they explained just 38 % of the variation of Cd concentration in pasture grasses.…”
Section: Change In Plant CD Concentration and Uptakementioning
confidence: 99%